Diseño y validación de dos escalas para medir el miedo al delito y la confianza en la policía - Fernández Molina, Esther (Revista Española de Investigación Criminológica, 2012)
In this paper, the design of two measures, fear of crime and confidence in the police, is presented, in order to work on the cultural significance of the fear of crime and achieve a rigorous instrument. The items proposed consider the multidimensionality of the workable definitions supported by recent research. Furthermore, confirmatory factor analysis (CFA) is used for validation process with a sample of Mexican university students. The data confirms the model fit. Confidence in the police has a twodimensional structure, while fear of crime has a three-dimensional composition. Finally, further research is suggested to improve the validity and reliability of the measures developed here.